Avoiding parasitical uses of global solidarity - Shults, Lee Michael (Frontiers in Human Dynamics, 2024)
This article critically engages the normative implications of referring to small-scale, "pop-up" aid actors as Citizen Initiatives for Global Solidarity (CIGS) in the context of citizen-initiated disaster and humanitarian response. The force of the term 'global solidarity' can be powerful, yet the precise meaning of the concept is often ambiguous. In light of this ambiguity, this article works towards conceptual clarity while questioning whether or not the label 'CIGS' is an instance of parasitical solidarity-a rhetorical use of global solidarity that implies more, or different, moral content than is actually present in the practices being described as solidaristic. While answers to that question will differ on a case-to-case basis, the conversations across regions and disciplines that this special issue aims to contribute towards will benefit from a careful consideration of how to avoid parasitical uses of global solidarity. In addition, sensitivity on this front is an important component of decolonizing the discourse of aid by decentering the roles of volunteers. Operationalizing global solidarity with an eye towards "pop-up" humanitarian responses generates a conceptual starting point that is required for these interdisciplinary conversations, regardless of whether that operationalization is ultimately utilized, adjusted, or rejected by those engaging disaster response from different standpoints.